Evaluating the Effect of Surgical Face Mask on Choroidal Thickness: Doi: 10.36351/pjo.v42i1.2204 - Gill, Rida e Noor; Saddiqi, Sadia; Habib, Athar; Zahid, Mawra (Pakistan Journal of Ophthalmology, 2025)
Purpose: To evaluate the choroidal thickness in healthcare professionals using a surgical face mask. Study Design: Cross sectional study. Place and Duration of Study: Ittefaq Hospital, Lahore, and Sohail’s Oculab from June 2023 to July 2024. Method: Sixty healthcare professionals aged 25–45 years with best corrected visual acuity of 6/6 or 6/9 and normal intraocular pressure (12–21 mmHg) were included. Participants with any systemic or ocular pathology were excluded. The instruments used in this study included a distance Snellen chart, an air-puff tonometer (Topcon), and a swept-source OCT device (Topcon DRI OCT Triton 3D). A self-structured proforma was used for data collection. Choroidal thickness was measured after wearing a surgical face mask for at least 4 hours and again 30 minutes after mask removal using swept-source OCT. Results: The study included the right eyes of 60 participants in which there were 34 males (58.3%) and 26 females (41.7%). The mean age was 30.35 ± 4.90 years. A paired-sample t-test showed a statistically significant change in choroidal thickness between 4 hours of mask wearing and 30 minutes after mask removal (p < 0.001). Conclusion: The findings showed a significant difference in choroidal thickness when wearing a surgical face mask compared with not wearing one. Prolonged mask use may cause hypercapnia, which can increase retinal vessel diameter and blood flow, leading to increased choroidal thickness.